Analysis of the Impact of the Social Environment on the Implementation of the Construction of the Wiego Warehouse Building on Jalan Letda Sujono Medan - Silvia B, Tri; Tanjung, Darlina; Simbolon, Ronal H T (CV. Rayyan Dwi Bharata, 2024)
In modern civilization, the construction of modern shopping centers is often a symbol of a city's progress. The implementation of development will definitely have various impacts, one of which is social and environmental impacts. This research aims to determine the social and environmental impact of the construction of the Wiego Warehouse Building on Jalan Letda Sujono. This research was carried out by distributing questionnaires to the local community during the construction of the project. The data collection technique used a questionnaire by distributing it to 71 respondents with question criteria of social impact and environmental impact. The research method used is descriptive analysis, validity testing and reliability testing. The results of the social and environmental impact validity test have a calculated r value greater than the r table, namely 0.2303, and the social impact reliability test results show a Cronbach Alpha value (0.935) 0.7, while the environmental impact Cronbach Alpha (0.974) 0, 7. The ranking method is used to determine the ranking of respondents and give priority to study variables, after collecting data from respondents, it is then analyzed using the Mean value, which is a group explanation technique based on the average value to get the Mean value, processing questionnaire data using the SPSS program with descriptive analysis methods. From the research results, a ranking order for each social and environmental impact was obtained. The most important social impact is disruption of traffic comfort, and the most important environmental impact is the effect of implementing this project on the emergence of air pollution.